Cancer incidence of workers in the Swedish petroleum industry. Issue 9 (September 1997) - Järvholm, B; Mellblom, B; Norrman, R; Nilsson, R; Nordlinder, R
Abstract : OBJECTIVES: To estimate the risk of cancer due to occupational exposure to petroleum products in the Swedish transport and refinery industries. METHODS: In a retrospective cohort study the cancer incidence in 4128 men and 191 women, who had worked for at least one year in the petroleum industry, was compared with the incidence in the general population. The job titles and employment times for each person were found in personal files in the industries. The men had on average worked in jobs exposed to petroleum for 11.6 years at the end of the observation period. The cases of cancer were identified by record linkage with the Swedish cancer register. RESULTS: In total there were 146 cases of cancer v 157.6 expected (standardised mortality ratio (SMR) 0.93 90% confidence interval (90% CI) 0.80 to 1.1). Operators at refineries had an increased risk of leukaemia (6 cases v 1.7 expected, 90% CI of relative risk (RR) 1.5 to 7.0). Five of the six cases had started to work at the refineries in the 1950s or later. No other significantly increased risk of cancer was found. Distribution workers had a decreased incidence of lung cancer (no cases, 90% CI of RR 0 to 0.4). CONCLUSIONS: Operators at Swedish refineries had an increased risk of leukaemia. A possible cause is exposure to benzene. There was no increased risk of leukaemia in distribution workers. Distribution workers had a decreased risk of lung cancer.